2005
DOI: 10.1063/1.2130383
|View full text |Cite
|
Sign up to set email alerts
|

Uncooled bolometer response of a low noise La2∕3Sr1∕3MnO3 thin film

Abstract: We report measurements of the optical responses of a La2/3Sr1/3MnO3 (LSMO) sample at a wavelength of 533 nm in the 300 -400 K range. The 200 nm thick film was grown by pulsed laser deposition on (100) SrTiO3 substrate and showed remarkably low noise. At 335 K the temperature coefficient of the resistance of a 100 µm wide 300 µm long LSMO line was 0.017 K -1 and the normalized Hooge parameter was 9×10 -30 m 3 , which is among the lowest reported values. We then measured an optical sensitivity at I = 5 mA of 10.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
(31 reference statements)
2
20
0
Order By: Relevance
“…It is defined as the ratio of the voltage spectral noise density times sample volume over the square of the sample voltage at 1 Hz. Values in the 4 × 10 −29 −4 × 10 −28 m 3 range were found, which are promising results since they are comparable to the values measured in LSMO of the same thickness deposited on standard STO(001) [8]. Therefore, in addition to the uniaxial magnetic anisotropy observed in the 40 nm thick films deposited on the 10…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is defined as the ratio of the voltage spectral noise density times sample volume over the square of the sample voltage at 1 Hz. Values in the 4 × 10 −29 −4 × 10 −28 m 3 range were found, which are promising results since they are comparable to the values measured in LSMO of the same thickness deposited on standard STO(001) [8]. Therefore, in addition to the uniaxial magnetic anisotropy observed in the 40 nm thick films deposited on the 10…”
Section: Discussionsupporting
confidence: 68%
“…the coercive field is the largest when the external field is along the step direction and vanishes when external field is perpendicular to the step direction. In the easy direction, the coercitive field was 11.6 Oe, which, is much higher than the one obtained on STO(001), which is 2.7 Oe in the [110] or [1][2][3][4][5][6][7][8][9][10] directions. At last Fig.…”
Section: Preliminary Magnetic Characterizationmentioning
confidence: 91%
“…Higher optical sensitivities can be reached by lowering the sample temperature and increasing the bias current, so that the maximum of dR/dT can be reached thanks to Joule effects. At room temperature, measurements presented in Figure 2a show that the maximum of sensitivity about 1000 V·W −1 is reached at a bias current of 187 µA compatible with the LSMO absorption (= 0.8) [4].…”
Section: Resultsmentioning
confidence: 92%
“…La0.7Sr0.3MnO3 (LSMO) is a very interesting material for the fabrication of infrared bolometers because of the large variation of its electrical resistance R with temperature T close to room temperature [2][3][4][5]. It has a large temperature coefficient of resistance, named TCR = 1/R × dR/dT, of about 0.02 K −1 in the 300-340 K range and it also shows a low noise level compared with other resistive materials such as semiconductors and other oxide materials [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] Technological interest has centered on solar cells, light-emitting diodes, and photoelectric detectors. [37,38] Previous researches showed that these materials represent good properties, such as ultrafast response, high-sensitivity, broad-spectrum and position-sensitivity, as optoelectronic device materials.…”
Section: Ultrafast Photoresponse In Oxide Filmsmentioning
confidence: 99%